Randomness Evaluation of Modified A5/1 Stream Cipher for Global System for Mobile Communication - Siti Yohana Akmal Mohd Fauzi; Marinah Othman; Farrah Masyitah Mohd Shuib; Kamaruzzaman Seman; Khairi Abdul Rahim (Universiti Sains Islam Malaysia, 2024)
While the A5/1 stream cipher encryption is known to aid in providing security and privacy for the mobile communication, it actually has numerous security vulnerabilities that leave it susceptible to attacks. Although newer technology standards have been developed, the majority of the mobile phones around the world still make use of the A5/1 stream cipher design, hence the urgent need to strengthen the latter. Numerous works have been done to improve the security of the A5/1, such as by altering its clocking mechanism, and the length of the linear feedback shift register, leading to the ultimate goal of producing a stream of random bits which are difficult to crack, with the National Institute of Standards and Technology (NIST) Statistical Toolsuite used to analyse the randomness property of the results. However, none of them, to the best of the author's knowledge actually carried out the analysis of the results according to the guideline as per recommended by the NIST, despite the fact that the interpretation of the results is crucial in determining the strength of the stream cipher, as to whether it is robust to attacks, or otherwise. In this paper, a new modified A5/1 stream cipher is proposed and tested using the NIST test suite. The results, interpreted according to the NIST guidelines, by analysing the proportion of sequences passing test and the uniformity of the P-value, shows that the new modified design is random and is a good alternative to the conventional A5/1 stream cipher. A selective review of the weaknesses of a few of the interpretations by the other researchers will also be included.